Challenges of General Practice Education in Iran: A Qualitative Study - Mohammadreza Amiresmaili; Mahmood Nekoei Moghadam; Mahmood Moosazadeh; Elaheh Pahlavan (Kerman University of Medical Sciences, 2013)
Background & Objective: According to some evidences medical graduates do not evaluate their skills and capabilities to perform professional responsibilities at an acceptable level In other words there is a disagreement among authorities and experts of medical education in this regard This study aimed to survey the challenges of general physicianeducation system in Iran Methods: This applied study was carried out by qualitative method A purposeful sample of 23 informants participated in the study Semistructured interview was applied for data collection and Data were analyzed using framework method Results A total of 23 subthemes classified under 6 major themes were identified Major themes included strategies of general practice education structural issues incomprehensiveness of courses and curriculum educational fields educational problems and resources Conclusion: Due to several issues the effectiveness of general physicianeducation in Iran is faced with serious challenges Incompatibility of education with real needs of the community is one of the most important issues Therefore generalphysician education should move toward becoming more practical and empowering medical students to manage health centers should be taken into account in a systematic and efficient manner